The use of kamusku application to increase student’s teaching english vocabulary - Purwanto, Indah Nur Chotimah; Sutopo, Anam (Cendikia : Media Jurnal Ilmiah Pendidikan, 2025)
This study investigates the use of the Kamusku application to enhance English vocabulary mastery among eleventh-grade students in the Computer and Network Engineering program at SMK Muhammadiyah 01 Boyolali, Central Java. Employing a qualitative descriptive case study approach, the research focused on the implementation of Kamusku, students’ motivations, challenges encountered, and strategies to overcome them. Data were collected through observation, online questionnaires completed by thirty-two students, and semi-structured interviews with five students and one English teacher using purposive sampling. Triangulation of sources and techniques ensured data validity, while analysis followed the steps of data reduction, display, and conclusion drawing. Findings reveal that students effectively integrated Kamusku into their learning routines at school and home, appreciating its ease of use, quick access to word meanings, offline mode, and practicality compared to conventional dictionaries. Challenges included application errors, limited storage, and offline translation constraints, which students overcame through device management and adaptive strategies. Overall, Kamusku supports independent and adaptive learning, enhancing vocabulary mastery and digital literacy, and offers practical implications for teachers, students, and schools to optimize technology-based English learning.